Comparative Assessment of Compliance Management Implementation in the Public and Private Sectors of Ukraine - Maryniuk, Ivan (Herald of Economics, 2026)
In modern conditions, transparency, accountability and effective management are becoming key for the public and private sectors. The implementation of compliance management contributes to compliance with legislation, the formation of an ethical culture and increasing trust in organizations. The purpose of the study is to develop an author’s system of criteria for evaluating the implementation of compliance management for the public and private sectors of Ukraine. To identify the specifics of the impact of sectoral specifics on the effectiveness of compliance functions and to offer recommendations for their improvement. Methods: comparative analysis, expert assessment and synthesis of practical experience, systemic. It was found that the assessment of compliance management has different specifics depending on the sector: in the banking sector it is focused on minimizing compliance risks and increasing business value, in the non-financial corporate sector – on internal organization and instrumental support, in state institutions – on compliance with legislation and preventive risk management. The proposed author’s system of criteria allows for a comprehensive assessment of the effectiveness of compliance management and the formulation of practical recommendations for their development. Prospects. The results of the study can become the basis for the further implementation of standardized compliance management assessment systems, harmonization of national practices with international standards, as well as the development of digital and innovative tools to increase transparency, efficiency and reputational impact of organizations.